Retail sector in the Republic of Moldova as a study framework - ROBU Elena (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
Retail marketing is the process by which retailers promote awareness and interest of their goods and services in an effort to generate sales from their consumers. Retail marketing is application of marketing functions in distribution of goods to the customers. Organized retail is not just selling of goods, it embraces activities of marketing like grading packing, promotion and advertisements and show casing variety of goods, at reasonable price with offers like discount, credit. Retail Marketing provides convenience, comfort in shopping in place or medium that is convenient to the consumer. Retail and marketing are two different concepts, whereas retail is selling in small desired quantity to the people, marketing includes set of functions like transportation banking, insurance, warehousing and promotion. The main purpose is to deliver the goods to the people that can result in customer satisfaction.